Impact of London's low emission zone on air quality and children's respiratory health: a sequential annual cross-sectional study. (January 2019) - Mudway, Ian S; Dundas, Isobel; Wood, Helen E; Marlin, Nadine; Jamaludin, Jeenath B; Bremner, Stephen A; Cross, Louise; Grieve, Andrew; Nanzer, Alex; Barratt, Ben M; Beevers, Sean; Dajnak, David; et al.
Summary: Background: Low emission zones (LEZ) are an increasingly common, but unevaluated, intervention aimed at improving urban air quality and public health. We investigated the impact of London's LEZ on air quality and children's respiratory health. Methods: We did a sequential annual cross-sectional study of 2164 children aged 8–9 years attending primary schools between 2009–10 and 2013–14 in central London, UK, following the introduction of London's LEZ in February, 2008. We examined the association between modelled pollutant exposures of nitrogen oxides (including nitrogen dioxide [NO2 ]) and particulate matter with a diameter of less than 2·5 μm (PM2·5 ) and less than 10 μm (PM10 ) and lung function: postbronchodilator forced expiratory volume in 1 s (FEV1, primary outcome), forced vital capacity (FVC), and respiratory or allergic symptoms. We assigned annual exposures by each child's home and school address, as well as spatially resolved estimates for the 3 h (0600–0900 h), 24 h, and 7 days before each child's assessment, to isolate long-term from short-term effects. Findings: The percentage of children living at addresses exceeding the EU limit value for annual NO2 (40 μg/m 3 ) fell from 99% (444/450) in 2009 to 34% (150/441) in 2013. Over this period, we identified a reduction in NO2 at both roadside (median −1·35 μg/m 3 per year; 95% CI −2·09 to −0·61; p=0·0004) and background locations (−0·97; −1·56 to −0·38; p=0·0013), but not for PM10 . The effect on PM2·5 was equivocal. We found no association between postbronchodilator FEV1 and annual residential pollutant attributions. By contrast, FVC was inversely correlated with annual NO2 (−0·0023 L/μg per m 3 ; −0·0044 to −0·0002; p=0·033) and PM10 (−0·0090 L/μg per m 3 ; −0·0175 to −0·0005; p=0·038). Interpretation: Within London's LEZ, a smaller lung volume in children was associated with higher annual air pollutant exposures. We found no evidence of a reduction in the proportion of children with small lungs over this period, despite small improvements in air quality in highly polluted urban areas during the implementation of London's LEZ. Interventions that deliver larger reductions in emissions might yield improvements in children's health. Funding: National Institute for Health Research Biomedical Research Centre at Guy's and St Thomas' National Health Service (NHS) Foundation Trust and King's College London, NHS Hackney, Lee Him donation, and Felicity Wilde Charitable Trust.